Biotechnological potential of Kuantan mangrove actinomycete, Micromonospora K3-13 - Mohd Omar, Suhaila; Zainal Abidin, Zaima Azira; Abdul Malek, Nur Fathiah; Mohd Farouk, Norsyafawati; Zainuddin, Zarina; Khan Chowdhury, Ahmed Jalal (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2016)
Introduction Mangrove is a complex and unique ecosystem which experiences periodical tidal flooding inundated with low, moderate and high saline water. The muddy soil is rich in organic matter derived from efficient nutrient cycling system and decomposition of mangrove leaves. Therefore, the adaptation of mangrove microorganisms towards these environmental factors could promote the production of interesting bioactive compounds and enzymes. Methodologies This study aimed to unravel the identity and biotechnological potential of a Kuantan mangrove actinomycete, strain K3-13, through morphology observation, molecular identification, antimicrobial test and xylan degradation test. Results The study revealed that this orange-coloured mycelium-forming isolate produced spores after long incubation period which showed characteristics that resembled Micromonaspora colonies. The phylogenetic analysis of the 16S rRNA gene sequence of strain K3-13 indicated that the highest similarity was to Micromonospora carbonacea DSM43168 (99%). Besides, K3-13 produced blue diffusible pigment upon cultivation on three different starch-agar medium. Cross streak assay conducted to detect antimicrobial activities indicated that K1-13 has strong antibacterial activities against Bacillus subtilis and Staphylococcus aureus. K3-13 also showed positive xylanase activities by exhibiting decolourization zone in the agar-based assay using azo-xylan as substrate. Conclusion Nevertheless, it can be concluded that Micromonospora K3-13 could be explored for its potential biotechnological application such as natural dye, antibacterial drugs and xylan biodegraders.